Separation and Characterization of Petroleum Sulfonate Components - Feng1, Ziyan; Cui1, Mingwei; Liu2, Jingjing; Song2, Yuhe; Qingsong Li2, Joshua (Asian Journal of Chemistry, 2014)
The objective of this research was to establish a systematic method to isolate and characterize petroleum sulfonate components. Petroleum sulfonate was separated into unsulfonated oil and oil-soluble components, an intermediate component and a hydrophilic component according to their polarities using column chromatography. Petroleum ether, 2-butanone, 95 % isobutanol and water were used as the eluent. The separation was monitored by infrared spectroscopy. The petroleum sulfonate components were characterized by elemental analysis and electrospray ionization-mass spectrometry. The experimental results showed that the petroleum sulfonate was composed of surfactant components with different polarities. The S and N contents increased with the increasing polarity of petroleum sulfonate components, whereas the average relative molecular mass decreased. The intermediate component, obtained by mixing with a water-soluble component at a 3:1 ratio, had the lowest interfacial tension.